2012
DOI: 10.1007/s12687-012-0113-1
|View full text |Cite
|
Sign up to set email alerts
|

Study of stillbirth and major congenital anomaly among newborns in the high-level natural radiation areas of Kerala, India

Abstract: Monitoring newborns for adverse outcomes like stillbirth and major congenital anomalies (MCA) is being carried out in government hospitals since 1995 in and around high-level natural radiation areas, a narrow strip of land on the southwest coast of Kerala, India. Natural deposits of monazite sand containing thorium and its daughter products account for elevated levels of natural radiation. Among 141,540 newborns [140,558 deliveries: 139,589 singleton, 957 twins (6.81 ‰), 11 triplets (0.078 ‰), and one quadrupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 29 publications
(36 reference statements)
0
23
0
Order By: Relevance
“…Nineteen studies that reported on prevalence of NTD among 547,803 new-borns were included. The birth prevalence of NTDs reported ranged from 0.5 per 1000 total births [ 22 ] to 18.2 per 1000 total births [ 13 ]. All the studies included in the meta-analysis were hospital based studies except one.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nineteen studies that reported on prevalence of NTD among 547,803 new-borns were included. The birth prevalence of NTDs reported ranged from 0.5 per 1000 total births [ 22 ] to 18.2 per 1000 total births [ 13 ]. All the studies included in the meta-analysis were hospital based studies except one.…”
Section: Resultsmentioning
confidence: 99%
“…Results from two studies [ 21 , 22 ] with gender specific prevalence of NTDs, shows the pooled prevalence of 2.3 cases per 1000 male births (95% CI 0.45 to 5.14) and 4.3 cases per 1000 female births (95% CI 1.90 to 10.41). There was no statistical evidence that NTD prevalence was higher in any gender.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The condition can be surgically repaired in some cases, but requires special care of the infant to prevent choking or aspiration until the surgery can be performed. Among the risk factors identified for cleft palate/lip are environmental pollutants, including radiation exposure [55]. Down syndrome, also Trisomy-21, features growth delays, similar facial and hand features and substantial intellectual deficits.…”
Section: Introductionmentioning
confidence: 99%